Experimental evaluation of safety and efficacy of plasma-treated poly-ε-caprolactone membrane as a substitute for human amniotic membrane in treating corneal epithelial defects in rabbit eyes - Raghav D Ravani (Indian Journal of Ophthalmology, 2021)
Purpose: To evaluate biocompatibility and safety of plasma-treated poly-ε-caprolactone (pPCL) membrane compared to the human amniotic membrane in the healing of corneal epithelial defects in an experimental model. Methods: This is a prospective, randomized animal study including 12 rabbits. Circular epithelial injury measuring 6 mm in diameter was induced over the central cornea of one eye in twelve rabbits. The rabbits were randomized into two groups; in group A, the defect was covered with human amniotic membrane, while in group B, an artificial membrane made of bio-polymer plasma-treated poly-ε-caprolactone was grafted. Six rabbits were euthanized after 1 month and the other six after 3 months and the corneal epithelium was evaluated histopathologically and with immunohistochemistry. Results: Light microscopy of the corneal tissue performed after 1 month and 3 months demonstrated similar findings with no significant complications in either group. Immunohistochemistry with anti-CK-3 antibody showed characteristic corneal phenotype in the healed epithelium. In eyes grafted with pPCL membrane, epithelial healing as estimated by a decrease in size of the defect was significantly better than the group treated with the human amniotic membrane at all time periods monitored (P < 0.05), except day 1 (P = 0.83). The percentage reduction in the size of the epithelial defect was also significantly more in the pPCL membrane group as compared to the human amniotic membrane at all time periods (P < 0.05 at all observations) post-implantation except day 1 (P = 0.73). Conclusion: Plasma-treated poly-ε-caprolactone membrane is safe, biocompatible, and effective in the healing of corneal epithelial defects in rabbits.